PENERAPAN MANAJEMEN RISIKO TERHADAP PERSAINGAN INDUSTRI CAFE DALAM UPAYA MEMPERTAHANKAN LOYALITAS PELANGGAN PADA CAFE MAHONI - Asrika Winana Farida Ayu; Rizka Asrina; Shopi Regina; Bahzatun Nur Harahap; Arsyadona Arsyadona (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The rapid growth of the café industry in urban areas has intensified competition, requiring each cafe to retain customer loyalty through effective business strategies. Cafe Mahoni, located in a strategic area, faces external challenges such as environmental noise and intense competition, as well as internal challenges related to managerial oversight and limited facilities. This study aims to analyze the application of risk management at Cafe Mahoni to maintain customer loyalty. Using Primary Data Analysis (PDA) methods through interviews, surveys, and observations, this research identifies risk factors and their handling strategies. The results show that facility rejuvenation, increased supervision frequency, and the implementation of service and product quality assurance standards play a vital role in maintaining customer satisfaction and loyalty, thereby enhancing Cafe Mahoni's competitiveness in the café industry.